Karakteristik Senyawa Kimia Ekstrak Ikan Gabus (Channa striata) dari Danau Tondano Menggunakan Fourier Transform Infra Red (FTIR) - Sangkal Ahlan; Supardi Rifani Hutami (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Snakehead fish (Channa striata) is a freshwater fish that is widely found in Indonesia. Snakehead fish has many benefits, including increasing albumin levels in the blood, increasing endurance, can heal wounds, both internal wounds, external wounds and post-operative wounds. The purpose of this study was to determine the character of the chemical compounds of snakehead fish extract in Lake Tondano. The method used for extraction is the Steaming method and analyzed using FTIR. The results of the study of Snakehead fish extract were analyzed in the FTIR computer application and obtained results showing 11 absorption band peaks. At the absorption band peaks of 3626.34 cm-1 and 3445.20 cm-1 indicate the O-H group suspected of having an alcohol compound. At the absorption band peak of 2097.19 cm-1 indicates the C = C group suspected of having an alkene compound. The peak of absorption band 1651.21 cm-1 and 1644.98 cm-1 indicates C=O group which is suspected to be amide compound I. The absorption band 1551.19 cm-1 indicates bending vibration of N-H group and stretching vibration of C-N which is suspected to be amide compound II. The absorption band 1458.33 cm-1 indicates CH3 group in the presence of collagen. The absorption band 1400.04 cm-1 indicates COO group which is suspected to be amino acid compound, aspartic acid and glutamic acid. The absorption band 1080.74 cm-1 indicates C-N group which is suspected to be amine compound. And the last absorption band is 562.15 cm-1 and 494.05 cm-1 indicates stretching vibration which indicates other compounds